인공심장판막의 연구개발 동향 - 한동근; 안광덕 (한국생체재료학회, 2005)
Heart disease is presently the major cause of death worldwide, with heart valve disease being one of the crucial afflictions of the cardiovascular system. If valve malfunction occurs, surgical repair or replacement of the diseased valve with a heart valve prosthesis is necessary to restore valve function. An estimated 87,000 heart valve replacement procedures were performed in U.S.A. in 2000, whereas about 275,000 procedures are done globally each year. A numbers of models for heart valve substitutes for past 40 years have been studied and developed, but currently two prosthetic heart valves were commercialized and used clinically: mechanical and tissue (bioprosthetic) valves in which approximately 55% are mechanical and 45% are tissue. However, both types of heart valves have many major complications and problems until now that limit their prolong success. A number of researches are being progressed to regenerate the ideal heart valves using tissue engineering. In this article, the following will give each characteristics of 4 kinds of valves including polymeric heart valves, an update of the recent developments, and current aspects of tissue-engineered heart valves.